Development of Organic Farming to Create a Environmentally Friendly Farming Which Has an Impact on Increasing the Quality and Quantity of Agricultural Productivity - Fathnur, Fathnur; Erif, La Ode Muhammad (Proceeding International Conference on Religion, Science and Education, 2026)
The purpose of this paper is to describe research findings that indicate that organic farming is increasingly being considered as a solution for improving soil quality and creating environmentally friendly agriculture. Environmentally friendly agriculture is a sustainable agricultural system that aims to improve, enhance, and maintain the quantity and quality of productivity by considering nutrient supply through the use of organic materials, minimizing dependence on inorganic fertilizers, improving soil biota, controlling plant pests (OPT) based on ecological conditions, and diversifying crops. Various innovative environmentally friendly agricultural systems have been developed based on good agricultural practices through synergy between technological components. The results explain that organic farming offers numerous benefits for improving soil quality and crop yields and has a more positive environmental impact compared to conventional agriculture. Environmentally friendly agriculture has strengths that outweigh its weaknesses, opportunities that outweigh its threats, and is socially sustainable, ensuring the sustainability of future agriculture and acceptance by users, especially farmers. It can also improve farmers' economic well-being.